2000
DOI: 10.1046/j.1365-2362.2000.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumour necrosis factor‐α levels in cancer patients are discontinuous and correlate with weight loss

Abstract: The present study demonstrates that TNF is intermittently or discontinuously detectable in patients with gastrointestinal cancer and that its levels correlate with the severity of weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…The positive correlation between weight loss and serum TNF alpha levels was also observed in other studies. Bossola et al [20] showed that Table 3. Severity data and evolution aspects of patients with tuberculosis and levels of TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation between weight loss and serum TNF alpha levels was also observed in other studies. Bossola et al [20] showed that Table 3. Severity data and evolution aspects of patients with tuberculosis and levels of TNF-alpha.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evaluations have linked protein catabolism to high levels of cytokines, particularly TNF-a [14,15]. It is the major mediator of cachexia observed in tumor patients (hence the other name cachectin) [16].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Increased TNF␣ levels were also associated with weight loss in patients with pancreatic carcinoma 12 and gastrointestinal carcinoma. 13 Nakashima et al 14 reported that TNF␣ contributed to the complex syndrome of cachexia in patients with CaP: TNF␣ was detected in 75% of patients with recurrent disease, and the body mass indices of patients with elevated serum TNF␣ levels were significantly lower compared with the corresponding values in patients with undetectable serum TNF␣ levels. However, some clinical studies failed to correlate TNF␣ levels with the cachectic state.…”
mentioning
confidence: 99%